Poly(A) Binding Protein Is Required for Nuclear Localization of the Ecdysteroidogenic Transcription Factor Molting Defective in the Prothoracic Gland of Drosophila melanogaster - Kamiyama, Takumi; Sun, Wei; Tani, Naoki; Nakamura, Akira; Niwa, Ryusuke (Frontiers in Genetics, 2020)
Steroid hormone signaling contributes to the development of multicellular organisms. In insects, ecdysteroids, like ecdysone and the more biologically-active derivative 20-hydroxyecdysone (20E), promote molting and metamorphosis. Ecdysone is biosynthesized in the prothoracic gland (PG), via several steps catalyzed by ecdysteroidogenic enzymes that are encoded by Halloween genes. The spatio-temporal expression pattern of ecdysteroidogenic genes is strictly controlled, resulting in a proper fluctuation of the 20E titer during insect development. However, their transcriptional regulatory mechanism is still elusive. A previous study has found that the polyadenylated tail [poly(A)] deadenylation complex, called Carbon catabolite repressor 4-Negative on TATA (CCR4-NOT) regulates the expression of spookier (spok), which encodes one of the ecdysteroidogenic enzymes in the fruit fly Drosophila melanogaster. Based on this finding, we speculated whether any other poly(A)-related protein also regulates spok expression. In this study, we reported that poly(A) binding protein (Pabp) is involved in spok expression by regulating nuclear localization of the transcription factor molting defective (Mld). When pabp was knocked down specifically in the PG by transgenic RNAi, both spok mRNA and Spok protein levels were significantly reduced. In addition, the spok promoter-driven green fluorescence protein (GFP) signal was also reduced in the pabp-RNAi PG, suggesting that Pabp is involved in the transcriptional regulation of spok. We next examined which transcription factors are responsible for Pabp-dependent transcriptional regulation. Among the transcription factors acting in the PG, we primarily focused on the zinc-finger transcription factor Mld, as Mld is essential for spok transcription. Mld was localized in the nucleus of the control PG cells, while Mld abnormally accumulated in the cytoplasm of pabp-RNAi PG cells. In contrast, pabp-RNAi did not affect the nuclear localization of other transcription factors, including ventral vein lacking (Vvl) and POU domain motif 3 (Pdm3), in PG cells. From these results, we propose that Pabp regulates subcellular localization in the PG, specifically of the transcription factor Mld, in the context of ecdysone biosynthesis.